Three lessons from accelerating scientific insight discovery via visual querying - Lee, Doris; Siddiqui, Tarique; Karahalios, Karrie; Parameswaran, Aditya (Patterns, 2020)
Exploratory data analysis is a crucial part of data-driven scientific discovery. Yet, the process of discovering insights from visualization can be a manual and painstaking process. This article discusses some of the lessons we learned from working with scientists in designing visual data exploration system, along with design considerations for future tools.